Making decisions: an analysis of styles and time pressure among selected graduate students in the Philippines - Ma. Leah Ulanday; Michael; Edgardo; Jordan; Rosemarie (Universidade Estadual de Alagoas, 2024)
The feeling of time pressure is a remarkable and significant phenomenon that people deal with throughout their lives. Empirical studies show that when people assume there are insufficient hours in the day and that they must work longer and harder than ever before, they experience feelings of time pressure, which in work contexts has led to job dissatisfaction, disconnection, poor performance, and absences because time constraints influence people's capabilities and the consequent effect on their decision-making processes. This study looks into how time pressure affects decision-making. This element has been identified as a critical decision- making determinant. Using a descriptive-correlational design, it identifies the impact of time pressure on the performance and decision-making styles among selected graduate students enrolled from different Universities in the Philippines. The study's findings determined respondents are frequently feel pressured with the work deadline and Unstable Workload has the lowest pressure points factor. Moreover, the results determined time pressure as a significant contributor to the decision- making of graduate students and indicates a favorable and significant relationship between time pressure and graduate students' decision-making styles. Furthermore, the study's findings provide useful insights into the difficulties that Graduate students experienced in managing their time in decision-making as professionals and students at the same time, and factors influencing student achievement and decision-making have been identified and analyzed.